СЕЛЕКЦИЯ УЧУН БОШЛАНГИЧ МАТЕРИАЛ ЯРАТИШДА G.HIRSUTUM L. ТУРИНИНГ ГЕНЕТИК САЛОҲИЯТИДАН ФОЙДАЛАНИШ - Сафиуллина, А.К.; Эрназарова, Д.Қ.; Кушанов, Ф.Н. (SCIENCE and SOCIETY, 2023)
It is known that the cotton species G.hirsutum L. has forms such as "yucatanense", "latifolium", "morrilli", "richmondii" and "religiosum", which still have no clear place in taxonomy, caused ambiguous views of a number of taxonomists.This article presents the indicators of crossbreeding and fecundity of seeds of F0 hybrids obtained with the participation of subspecies and forms of cotton of the species G.hirsutum L.